1999
DOI: 10.2114/jpa.18.81
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses to Maximal Treadmill and Deep Water Running in the Young and the Middle Aged Males.

Abstract: Abstract. In this study we investigated the effects of age factors on physiological responses to deep water running (DWR) compared with those of treadmill running (TMR) while the water and ambient temperatures were kept in thermoneutral conditions. Fourteen young healthy non-smoker males (Age = 20.4 -3.3 years, Height = 170.7 -6.2 cm, Weight = 65.1 -11.4 kg) and fourteen middle aged healthy non-smoker males (Age = 38.6 -4.4 years, Height = 171.8 -4.7 cm, Weight = 75.4 -9.6 kg) were selected for the study. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
0
18
1
4
Order By: Relevance
“…This control was performed with the aim to avoid interference in the collected variables. Moreover, the participants were familiarized with the Borg's scale (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This control was performed with the aim to avoid interference in the collected variables. Moreover, the participants were familiarized with the Borg's scale (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Methodsmentioning
confidence: 99%
“…However, this statement is questioned by some authors who state that during pregnancy many physiological variables are altered and this fact may alter their perceived exertion to exercise [7][8][9] . In the literature, there are studies which measure the role of the RPE in the prescription of different exercise modalities [10][11][12][13][14] and have been also used in investigations which need to prescribe the exercise intensity in different environment [15][16][17] . When analyzing the investigations found on RPE in different exercise modalities on land, we observed that there are clashing opinions about the RPE use for pregnant women 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Kruel (2000) , 1991;NAKANISHI et al, 1999aNAKANISHI et al, , 1999bDOWZER et al, 1999;TIGGEMANN et al, 2007;KANITZ, 2010), no entanto são poucos os que avaliam nos diferentes exercícios de hidroginástica (BEILKE, 2008;ALBERTON et al, 2007;ALBERTON et al, 2009 …”
Section: Respostas Submáximas De Exercícios No Meio Aquáticounclassified
“…Resultados encontrados também por Alberton et al (2007) Com relação às respostas de FC max, já é bem documentado na literatura as diferenças entre os meios aquático e terrestre, com respostas significativamente menores para o meio aquático (TOWN & BRADLEY, 1991;NAKANISHI et al, 1999aNAKANISHI et al, , 1999bDOWZER et al, 1999;TIGGEMANN et al, 2007;BEILKE, 2008 …”
Section: Respostas De Consumo De Oxigêniounclassified
“…Já Nakanishi et al (34) também encontraram redução significativa de 4,7bpm na FC de repouso em imersão na água. Todos os indivíduos eram do sexo masculino e permaneceram com a cabeça para fora da água e o corpo em flutuação pelo uso de um cinturão flutuador comparado com a posição sentada em ambiente terrestre.…”
Section: Comportamento Da Frequência Cardíaca De Repouso Durante a Imunclassified